Rooting biostimulants for Coffea arabica L. cuttings - Azevedo, Hariana Paula; Carvalho, Alex Mendonça; Rodrigues, Joyce Doria; Vidal, Douglas Alves; Santos, Heloisa Oliveira (Coffee Science - ISSN 1984-3909, 2020)
In the rooting process of Arabica coffee cuttings, plant hormones are used for inducing root formation. However, synthetic molecules cannot be used to form organic seedlings. The objective of this work was to evaluate the effect of nut grass extract and different concentrations and types of humic substances on Arabica coffee cuttings. Arabica coffee shoots were collected, and cuttings containing at least two buds were taken. The experiment had a three-factor design, 2 (without or with nut grass extract) x 2 (humic or fulvic acid) x 4 (0, 10, 25 and 50 mg.dm-³). The following vegetative data were evaluated: shoot height (cm), survival, remaining leaves, leaf pairs, vigor and number of shoots. The root length, area, volume, diameter, and fresh and dry mass were also evaluated. The enzyme activity of H+-ATPase, catalase, superoxide dismutase, alcohol dehydrogenase and esterase was also quantified. The results showed that the Arabica coffee cutting rooting rate was increased when treated with humic acid at a concentration of 10 mg.dm-³ in the presence of nut grass extract. The lowest oxidative stress was observed in the 10 mg.dm-³ humic and fulvic acid treatments, regardless of the use of the extract. Key words: Root system; IBA; humic acid; fulvic acid; shoots.